2020
DOI: 10.33596/coll.50
|View full text |Cite
|
Sign up to set email alerts
|

Community Partners as Service-Learning Co-Leaders

Abstract: Community partners contribute to fostering and sustaining service-learning partnerships. In the service-learning pedagogy, their leadership roles, although identified as partners and co-collaborator, have been under-investigated in the context of their perceptions and contributions. To contribute to the understanding of partners' collaborative involvement, and leadership strategies, we interviewed four partners from two non-profit agencies that had collaborated on projects with a small liberal arts university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…In practice, this means centering the goal of just relationships (rather than the service or the learning) as the starting point for ethical service-learning. Our findings build on previous studies that have shown the importance of relationships from the perspective of community partners (Clayton et al, 2010;Glover & Silka, 2013;Goldberg & Atkins, 2020;Sandy & Holland, 2006;Shore, 2006;Stoecker & Tryon, 2009;Tinkler et al, 2014). However, we believe that the findings in our study, which help to show how community partners perceive and articulate ethical service-learning, contribute additional insights to promote future research and practice grounded in this relational approach to service-learning ethics.…”
Section: Discussionsupporting
confidence: 88%
“…In practice, this means centering the goal of just relationships (rather than the service or the learning) as the starting point for ethical service-learning. Our findings build on previous studies that have shown the importance of relationships from the perspective of community partners (Clayton et al, 2010;Glover & Silka, 2013;Goldberg & Atkins, 2020;Sandy & Holland, 2006;Shore, 2006;Stoecker & Tryon, 2009;Tinkler et al, 2014). However, we believe that the findings in our study, which help to show how community partners perceive and articulate ethical service-learning, contribute additional insights to promote future research and practice grounded in this relational approach to service-learning ethics.…”
Section: Discussionsupporting
confidence: 88%
“…The second section provides historical insights about the evolving Age-friendly Auckland Project [34,35] highlighting the two SAP's achievements. Section three situates and elaborates on methodological challenges associated with autoethnographic inquiries [36] as a segue to the fourth section describing the processes involved in using relational leadership interview prompts [37,38] to elicit the narratives of older co-researchers active in progressing Tāmaki Makaurau Auckland's evolving Age-friendly City (AFC) agenda [39]. Section five describes the research participants, and section six explains the methods used to analyse the interview transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…Temporal flux is apparent in the fifteen relational leadership interview prompts that were originally developed to glean how service-learning partnerships between community agencies and institutions of higher learning in New England (USA) evolved over time [37]. Enhancing understanding of community partnership processes and outcomes in organisations hosting tertiary students, the interview prompts focused specifically on revealing the voices of community partners to elucidate "their knowledge, attitudes and skills" so that "deeper insights can be mined about growing and sustaining partnerships" [38] (p. 2). Furthermore, three specific leadership proficiencies of: knowing (especially sharing a common purpose to facilitate empowering participatory citizenship through ethical decision making that promotes and supports community processes); being (especially expressing hopeful commitments to socially responsible power sharing that promotes equity, values integrity and develops systems thinking perspectives); and doing (especially involving others in co-creating visions to identify goals, build coalitions and nurture reflective learning capacities) proved to be foundational in collective cooperative relationships among people striving to achieve positive change [70].…”
Section: Interview Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Per comprendere i risultati dell'analisi, occorre far riferimento al concetto di leadership, e in particolare alla leadership distribuita per l'equità e l'apprendimento (Distribuited Leadership for Equity and Learning -DLE). Quest'ultima appartiene all'intera organizzazione di riferimento nel suo complesso e viene esercitata da ogni suo membro che mette a disposizione le proprie competenze, esperienze e idee al fine di cooperare per sostenere un apprendimento inclusivo e olistico (Woods, 2015;EPNoSL Project, 2015;Goldberg & Atkins, 2020). La DLE si riferisce alla leadership di docenti, studenti, personale scolastico e partner territoriali coinvolti nell'organizzazione, i quali operano insieme sostenuti da una cultura condivisa, la quale valorizzi la partecipazione attiva, la crescita e il benessere in senso olistico e i valori di giustizia sociale e di cittadinanza democratica.…”
Section: La Leadership Distribuita E Il Service Learningunclassified